#Cleft: The use of Social Media Amongst Parents of Infants with Clefts. (August 2018) - Khouri, Joseph S.; McCheyne, Melisande J.; Morrison, Clinton S.
Introduction: Many societies and organizations are using social media to reach their target audience. The extent to which parents of patients with craniofacial anomalies use social media has yet to be determined. The goal of this study is to characterize and describe the use of social media by the parents of children with cleft lip and palate as it pertains to the care of their child. Materials and Methods: Parents or guardian of all patients presenting for initial consultation regarding a child's congenital cleft anomaly were contacted by phone or mail to complete a survey regarding their use of social media vis-à-vis their child's cleft anomaly. Participants were asked to answer a 19-question survey. Results: Thirty-two families were contacted and 25 surveys were completed. Ninety-two percent of respondents used social media to learn about their child's diagnosis. Facebook (76%) and blogs (24%) were the most commonly accessed social media outlets, followed by Instagram (8%). Education about the diagnosis and treatment of cleft pathology (87%) was the most common reason for accessing social media, followed by companionship and support (56%), and advice about perioperative care (52%). Almost half (43%) of parents used social media to obtain information on their caregiver and treatment team, and 26% of parents used information gained on social media to guide their decision on where to seek care. Conclusion: Social media is a readily available resource, one that will certainly shape the experiences of our patients and families for years to come.